2019
DOI: 10.1155/2019/3901907
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Retention and Clearance in the Diabetic Brain after Administrations of Gadodiamide, Gadopentetate Dimeglumine, and Gadoterate Meglumine in a Rat Model

Abstract: Purpose. To evaluate gadolinium (Gd) retention and clearance in the brain of diabetic rats after administrations of gadodiamide, gadopentetate dimeglumine, and gadoterate meglumine. Materials and Methods. Both diabetic rats (n = 52) and normal rats (n = 52) intravenously received 20 injections of 0.6 mmol Gd/kg gadodiamide, gadopentetate dimeglumine, gadoterate meglumine, or saline. Both diabetic rats and normal rats were divided into 2 subgroups of 24 and 28 rats for the 7-day and 42-day evaluations (i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Perivascular, Gd-containing deposits were also reported in the olfactory bulb of rats treated with linear GBCAs (gadodiamide and gadopentetate) but not the macrocyclic agent gadoterate. 58 Colocation of Gd with P in the vicinity of vessels 35,42 is consistent with the precipitation of Gd in the form of GdPO 4 present in the sea urchin-shaped deposits found. 82 This phenomenon might result from transmetallation with calcium, a metal crucial for the tight regulation of cerebral blood flow at the level of the neurovascular unit.…”
Section: Blood Cerebrospinal Fluid Barrier Access Pathwaysupporting
confidence: 71%
See 3 more Smart Citations
“…Perivascular, Gd-containing deposits were also reported in the olfactory bulb of rats treated with linear GBCAs (gadodiamide and gadopentetate) but not the macrocyclic agent gadoterate. 58 Colocation of Gd with P in the vicinity of vessels 35,42 is consistent with the precipitation of Gd in the form of GdPO 4 present in the sea urchin-shaped deposits found. 82 This phenomenon might result from transmetallation with calcium, a metal crucial for the tight regulation of cerebral blood flow at the level of the neurovascular unit.…”
Section: Blood Cerebrospinal Fluid Barrier Access Pathwaysupporting
confidence: 71%
“…1). 27,57,58 To our knowledge, no T 1 signal enhancement has been reported so far in olfactory bulbs in humans or rats. Of note is that the olfactory bulb is about 0.01% of the human brain by volume and 2% of the mouse brain by volume.…”
Section: Organ Levelmentioning
confidence: 86%
See 2 more Smart Citations
“…Consistent with previous studies, our study showed that the amount of retained Gd in mice exposed to linear neutral GBCAs Gd was much higher than that in animals exposed to macrocyclic neutral GBCAs gadoteridol. [33][34][35][36][37] However, in all brain regions in mice treated with gadoterate meglumine, the amount of retained total Gd was significantly higher than that in the control group. After administration of gadoterate meglumine, the total amount of Gd in the brain corresponded entirely to the intact gadoteridol.…”
Section: Discussionmentioning
confidence: 89%